2022
DOI: 10.1111/jdv.18641
|View full text |Cite
|
Sign up to set email alerts
|

Patient Unique Stigmatization Holistic tool in dermatology (PUSH‐D): Development and validation of a dermatology‐specific stigmatization assessment tool

Abstract: Background The skin plays an important role in establishing interpersonal relationships, and thus visible skin disorders, which have a significant impact on physical appearance, influence other people's behaviours and attitudes. Objective To develop and validate a dermatologic‐specific questionnaire to evaluate stigmatization in individuals with visible skin conditions. Methods Items were generated by a verbatim report based on qualitative interviews with patients with various dermatologic conditions. Subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…face, neck, hands and genitals) were assessed using the Self‐Assessment Vitiligo Extent Score (SA‐VES) 10 . QoL patient‐reported outcomes (PROs) included the EuroQoL 5‐Dimensions 5‐Levels questionnaire (EQ‐5D‐5L; range, 0–1 [lower scores indicate greater burden]), 11 Dermatology Life Quality Index (DLQI; range, 0–30 [higher scores indicate greater impairment]), 12 Patient Unique Stigmatization Holistic Tool in Dermatology (PUSH‐D; range, 0–85 [higher scores indicate greater stigma]), 13 Vitiligo Impact Patient scale (VIPs; range, 0–95 [higher scores indicate greater burden]), 14 Vitiligo‐specific Quality of Life (VitiQoL; range, 0–90 [higher scores indicate greater burden]) 15 assessment and the Center for Epidemiologic Studies Depression Scale (CES‐D; range, 0–60 [higher scores indicate more depression symptoms]) 16 . The 2022 questionnaire also collected data regarding nonprescription treatment.…”
Section: Methodsmentioning
confidence: 99%
“…face, neck, hands and genitals) were assessed using the Self‐Assessment Vitiligo Extent Score (SA‐VES) 10 . QoL patient‐reported outcomes (PROs) included the EuroQoL 5‐Dimensions 5‐Levels questionnaire (EQ‐5D‐5L; range, 0–1 [lower scores indicate greater burden]), 11 Dermatology Life Quality Index (DLQI; range, 0–30 [higher scores indicate greater impairment]), 12 Patient Unique Stigmatization Holistic Tool in Dermatology (PUSH‐D; range, 0–85 [higher scores indicate greater stigma]), 13 Vitiligo Impact Patient scale (VIPs; range, 0–95 [higher scores indicate greater burden]), 14 Vitiligo‐specific Quality of Life (VitiQoL; range, 0–90 [higher scores indicate greater burden]) 15 assessment and the Center for Epidemiologic Studies Depression Scale (CES‐D; range, 0–60 [higher scores indicate more depression symptoms]) 16 . The 2022 questionnaire also collected data regarding nonprescription treatment.…”
Section: Methodsmentioning
confidence: 99%
“…6 Our results suggest that PUSH-D, DLQI, EQ-5D and Epworth tools are also relevant for measuring the consequences of CP. In our study, we used for the first time after its validation the newly developed PUSH-D. 3 To our knowledge, there is only another study showing that stigmatization levels were high in CP 7 but this study was focused on body dysmorphia and stigmatization was only a covariate in multivariate models and was not analysed in the single diseases. The authors showed that feelings of stigmatization were significantly related to body dismorphic disorder symptoms using the Perceived Stigmatization Questionnaire.…”
Section: E909mentioning
confidence: 99%
“…1 We were interested in its impact on daily life and stigmatization.A self-administered questionnaire was distributed to members of the French patient advocacy group Association France Prurigo Nodulaire and to outpatients with CP from 2 departments of dermatology. Validated tools were used: Dermatology Life Quality Index (DLQI; score from 0 to 30), 2 Patient Unique Stigmatization Holistic tool in Dermatology (PUSH-D; score from 0 to 88), 3 EuroQol-5 Dimensions-3 Levels (EQ-5D-3L) utilities (score from −1 to 1) and visual analogic scale (VAS; from 0 to 100) 4 and Epworth sleepiness scale (score from 0 to 24). 5 Seventy patients were recruited, mostly women (n = 43, 61.4%).…”
mentioning
confidence: 99%